Review: analysis of optimal conditions of bovine serum albumin (BSA) protein denaturation inhibition method in anti-inflammatory activity testing of various plant leaf extracts - Nirmala, Annisa Rizka; Permatasari, Lina; Muliasari, Handa; Deccati, Rizqa Fersiyana (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Inflammation is a manifestation of the immune response to eliminate antigens and a process to respond to tissue damage. There are various drugs to control and suppress inflammation, referred to as anti-inflammatory agents. One method to test anti-inflammatory activity is the inhibition of Bovine Serum Albumin (BSA) protein denaturation. This review article will discuss the stages and optimal conditions in the inhibition of BSA protein denaturation method using various leaf extract samples. Literature was gathered from several journal database websites such as PubMed, ScienceDirect, and Google Scholar with keywords